2013
DOI: 10.1186/1751-0147-55-44
|View full text |Cite
|
Sign up to set email alerts
|

Individual risk factors for Mycoplasma hyopneumoniae infections in suckling pigs at the age of weaning

Abstract: BackgroundIn recent years, the occurrence and the relevance of Mycoplasma hyopneumoniae infections in suckling pigs has been examined in several studies. Whereas most of these studies were focused on sole prevalence estimation within different age groups, follow-up of infected piglets or assessment of pathological findings, none of the studies included a detailed analysis of individual and environmental risk factors. Therefore, the aim of the present study was to investigate the frequency of M. hyopneumoniae i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 34 publications
4
24
2
2
Order By: Relevance
“…Females under the age of 1 year are more strongly affected. Our findings are in agreement with Nathues et al [19] who also reported gender difference in the incidence of Mycoplasma hyopneumoniae in suckling pigs. They found 56.1% incidence in females compared to 43.9% in males.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Females under the age of 1 year are more strongly affected. Our findings are in agreement with Nathues et al [19] who also reported gender difference in the incidence of Mycoplasma hyopneumoniae in suckling pigs. They found 56.1% incidence in females compared to 43.9% in males.…”
Section: Discussionsupporting
confidence: 94%
“…A total number of 459 samples were tested from pigs for M. hyopneumoniae, out also reported more seropositivity in younger age pigs [9] [18] [19]. In another study Grosse et al [20] found older sows in some herds in Germany more often seropositive than younger ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The function parameters were selected in order to reproduce observed prevalence of M. hyopneumoniae infections in suckling pigs [22]. …”
Section: Methodsmentioning
confidence: 99%
“…The likelihood of transmission of M. hyopneumoniae from sows to their offspring increased exponentially with the length of the suckling period, which is equal to the time under exposure [22, 26, 27]. Two scenarios assuming a length of the suckling period equal to 21 and 28 days, respectively, were tested.…”
Section: Methodsmentioning
confidence: 99%